Islamic Boarding Schools Management Strategies in Conducting Illegal Moneying Students - Muhammad Mushfi El Iq Bali; Kamilia Zulqornain (MANAZHIM, 2023)
Nurul Jadid Paiton Probolinggo Islamic Boarding School is one of the largest Islamic boarding schools in the East Java region, located on Jl. Kyai Zaini Mun'im in Karanganyar Village, Paiton, Probolinggo, founded by KH. Zaini Mun'im, in 1948 one of the Islamic boarding schools that implemented the modern system. However, they still apply the old pattern by accepting updates without changing the teachings of the Qur'an and Al-Hadith. With the guidance that he directs to the surrounding community, little by little, they learn to understand the importance of religious knowledge. This study aims to analyze the management strategy of Islamic boarding schools in tackling students' illegal money in transactions conducted at the Nurul Jadid Paiton Islamic Boarding School, Probolinggo. Pondok Pesantren Nurul Jadid Paiton Probolinggo has implemented the use of E-Provision services for students or digital money since early 2017. This research uses qualitative case study research conducted through observation and interviews. Data analysis was carried out through data presentation, data reduction, and conclusions. The results of the study show that Nurul Jadid students still use cash in transactions, so Nurul Jadid students need help to manage daily financial expenses determined by their parents; each of them exceeds the limit set in the student's E-Bekal. However, E-Provision management has provided good facilities, served as well as possible and served extra to overcome problems and help provide satisfaction for students and guardians.